Hierarchical clustering analysis of reading aloud data: a new technique for evaluating the performance of computational models - Robidoux, Serje; Pritchard, Stephen (Frontiers in Psychology, 2014)
DRC (Coltheart et al., 2001) and CDP++ (Perry, Zorzi, & Ziegler, 2010) are two of the most successful models of reading aloud. These models differ primarily in how their sublexical systems convert letter strings into phonological codes. DRC adopts a set of grapheme-to-phoneme conversion rules (GPCs) while CDP++ uses a simple trained network that has been exposed to a combination of rules and the spellings and pronunciations of known words. Thus far the debate between fixed rules and learned associations has largely emphasized reaction time experiments, error rates in dyslexias, and item-level variance from large-scale databases. Recently, Pritchard, Coltheart, Palethorpe, and Castles (2012) examined the models’ nonword reading in a new way. They compared responses produced by the models to those produced by 45 skilled readers. Their item-by-item analysis is informative, but leaves open some questions that can be addressed with a different technique. Using hierarchical clustering techniques, we first examined the subject data to identify if there are classes of subjects that are similar to each other in their overall response profiles. We found that there are indeed two groups of subject that differ in their pronunciations for certain consonant clusters. We also tested the possibility that CDP++ is modeling one set of subjects well, while DRC is modeling a different set of subjects. We found that CDP++ does not fit any human reader’s response pattern very well, while DRC fits the human readers as well as or better than any other reader.